Efficacy of Modified Nonpneumatic Transaxillary Approach in the Treatment of Thyroid Cancer and Its Effect on Immune Function and Parathyroid Function - Tao Huang; Yiming Sang; Jizong Zhang (Emergency Medicine International)
Objective. The aim of the study is to investigate the effect of modified nonpneumatic transaxillary approach in the treatment of thyroid cancer and its effect on immune function and parathyroid function. Methods. A total of 96 patients with thyroid cancer who were diagnosed and treated in our hospital from January 2018 to December 2020 were selected and randomly divided into the control group of 48 cases and the observation group of 48 cases. The control group was given open surgery, and for the observation group, modified nonpneumatic transaxillary approach was used for treatment. The perioperative related indicators, the incidence of complications, as well as the changes of immune function indicators, parathyroid hormone (PTH), and calcium before and after surgery were compared between the two groups. Results. The time of flap separation and cavity construction, operation time, and hospital stay in the observation group were significantly longer than those in the control group (P < 0.05). After operation, CD3+, CD4+, and CD4+/CD8+ in the two groups were lower than those before operation (P < 0.05), but the observation group was significantly higher than that in the control group (P < 0.05). The serum PTH and calcium at 1 h, 1 d, 3 d and 7 d after operation were lower than those before operation in this group (P < 0.05), but the observation group was significantly higher than that in the control group (P < 0.05). Compared with the control group, the incidence of complications in the observation group (4.17% vs. 6.25%) was not statistically significant (P > 0.05). Conclusion. Compared with open surgery, the modified nonpneumatic transaxillary approach in the treatment of thyroid cancer is more effective in reducing immune function decline, hypoparathyroidism, and hypocalcemia; although the operation time and recovery time are longer, and it is safe. Sex is also high.